A rate control scheme using multi block size BMA for DWT-based video compression with constant quality - Park, SJ; Kim, HJ; Park, MC (IEICE-INST ELECTRONICS INFORMATION COMMUNICATIONS ENG, 2004)
Modem video compression usually consists of ME/MC (Motion Estimation/Motion Compensation), transform, and quantization of the transform coefficients. Efficient bit allocation technique to distribute available bits to motion parameters and quantized coefficients is an important part of the whole system. A method that is very complex and/or needs buffering of many future frames is not suitable for real time application. We develop an efficient bit allocation technique that utilizes the estimated effect of allocated bits to motion parameter and quantization on the overall quality. We also propose an hierarchical block based ME/MC technique that requires less computations than classical BMA (Block Matching Algorithm) while offering better motion estimation.
Keywords: BIT ALLOCATION; IMAGE